Organizational structure in Icelandic companies before and after the financial crisis - Steinþórsson, Runólfur Smári; Þórarinsdóttir, Anna Marín; Svansson, Einar (Research in applied business and economics, 2018)
This paper discusses the development of organizational structure in Icelandic enterprises before and after the economic crash in 2008. This is built on data compiled in the Innform research project in Iceland, first from the precrash years 2004 to 2007 and second the postcrash years 2010 to 2014. A comparison is also drawn up with an overview of the five published research results about the structure of Icelandic companies in the period of 20042016. The purpose of this article is to describe the main characteristics of the organizational structure of Icelandic companies and their evolution. At the same time the aim is to look for changes after the economic crash in 2008 on different management practices related to organizational structure. The main findings point to the direction that organizational structure has partly changed. Especially with more focus on effectiveness and internal processes. Empowerment has increased with correlation to matrix structure and project structure which are increasingly in use. Previous research shows that most big Icelandic companies are using both functional and divisional structure, that relates to a mixed structure. The functional structure is the overarching form in both the smaller and bigger companies. It looks like a flux period in the structure in the first years after the crash, where the focus of the directors on formal structure dwindled temporarily. Viðfangsefni greinarinnar er þróun á skipulagi fyrirtækja á Íslandi fyrir og eftir fjármálahrunið árið 2008. Byggt er á rannsóknum í verkefninu Innform á Íslandi, annars vegar frá 2004 til 2007 og hins vegar frá 2010 til 2014. Einnig er gerður samanburður á milli fimm rannsókna sem gerðar hafa verið um skipulag fyrirtækja á Íslandi á árunum fyrir og eftir hrun. Markmið greinarinnar er að lýsa megineinkennum á stjórnskipulagi íslenskra fyrirtækja og gera grein fyrir þróun á skipulagi þeirra. Jafnframt er markmiðið að kanna hvort sjá megi breytingar á skipulagi íslenskra fyrirtækja eftir efnahagshrunið 2008 á ýmsum ...